Design and analysis of the airfield lighting system (ALS) precision approach lighting system (PALS) on runway 14 Kertajati International Airport Majalengka - Aep Ma'shum Nurzaman (Journal of Emerging Innovations in Engineering, 2025)
This study analyzed the design and implementation of the Precision Approach Lighting System (PALS) for Runway 14 at Kertajati International Airport, Majalengka. A qualitative case study approach was employed, combining field measurements, semi-structured interviews with airport operators and technicians, and document analysis based on ICAO Annex 14 Volume I and Indonesian regulation KP 326/2019. Field measurements determined precise lamp positions using theodolite equipment across 30 barrettes at 30-meter intervals, spanning 900 meters. Ground elevation assessments revealed variations from 0.0m to 5.75m, necessitating customized pole configurations ranging from 2.1m to 4.6m. Electrical system calculations determined a 25 KVA Constant Current Regulator (CCR) capacity with 7/8 tapping configuration, optimizing circuit loads at 74.42% and 77.48%. Primary cable lengths of 5,259m and 5,134m were calculated with 16mm² cross-sectional area for adequate power distribution. The integration of PALS with existing Instrument Landing System (ILS) enabled Category I precision approach capability, significantly enhancing aviation safety during low-visibility conditions. The design fully complied with international standards and supported Kertajati's operational capacity enhancement from 8 to 300 daily aircraft movements, establishing comprehensive all-weather operational capability.